Advanced pilot modeling for rotorcraft handling qualities investigation in turbulent wind - Ji, H.; Lu, L. (My University, 2021)
Turbulent wind is known notoriously that can significantly deteriorate rotorcraft performance and handling qualities for manoeuvring flight. However, research on this topic is rarely reported largely due to the lack of an effective analytical tool. This paper develops a pilot model to explore the effect of turbulent wind on rotorcraft handling qualities. The proposed pilot model consists of three components: a compensatory control model for attitude stabilization, a preview control model for trajectory tracking, and a tau guidance model for trajectory planning. Model accuracy assessment indicates that the new pilot model can plan and track a desired trajectory conforming to pilot’s tau guidance strategy and predict credible handling qualities capturing the effect of the vestibular system and a flight control system. Handling qualities analysis for a slalom task in turbulent wind shows that the new pilot model predicts the effect of mean wind on rotorcraft manoeuvring aggressiveness and yaw control performance by changing required ground speed and the airflow through the tail rotor. Atmospheric turbulence significantly deteriorates the task with increased turbulence intensities. Flight control system can significantly improve the tracking performance and HQs in turbulent wind but saturation due to limited authority in aggressive operation reduces the effect of the flight control system.